CSC788: Data Visualization / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
This course is an introduction to key design principles and techniques for visualizing data. The aim of this course is to understand how visual representations can help in analysis and understanding of complex data. After taking this course, students should be able to critique presented visualizations and identify the design principles that were used to create them. Furthermore, the students should be able to construct and evaluate their own visualization work.